SELF EFFICACY AND LIFE SATISFACTION AMONG YOUNG ADULTS (International Journal of Food and Nutritional Sciences, 2022)
Self-efficacy and life satisfaction are important factors for young adults. Self-efficacy is a person’s belief in their capacity and capability to exercise some measures of control over their functioning and over environmental events. Self-efficacy is important for young adults because it helps them achieve their goals. Life satisfaction is the way a person perceives how his or her life has been and how they feel about how it is going in the future, and it is a measure of wellbeing. The objective of the study is to find out if self-efficacy increases life satisfaction in young adults. The sample consisted of 240 students belonging to the age range of 18 to 24 years from rural and urban areas. The tools used to assess self-efficacy and life satisfaction were the Self-Efficacy Scale (Ralf Schwarzer, Matthias Jerusalem, 1993) and the Life Satisfaction Scale, respectively. The results were analyzed using a two-way analysis of variance. The results showed that there is no significant gender difference in self-efficacy or life satisfaction. There is a significant difference between urban and rural young adults in their level of life satisfaction. Mean scores indicated that rural young adults showed a significantly higher level of life satisfaction compared to urban young adults. A significant difference in the level of self-efficacy was not found between urban and rural young adults.